1968
DOI: 10.1037/h0026834
|View full text |Cite
|
Sign up to set email alerts
|

Modification of smoking behavior: A review.

Abstract: Within the framework of therapy-outcome research, behavior-modification approaches to the treatment of smoking are reviewed and evaluated. Case reports, studies without control groups, and the few controlled comparisons of 2 or more treatment methods are considered separately; the behavioristic techniques are then compared against the more traditional smoking treatments (withdrawal clinics, drug treatments, group therapy). Though the lack of standardized methodology and the wide variation in subject-selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Keutzer and associates' careful study evaluated several techniques. They revealed a 23 percent success rate at the end of treatment and 12 percent at the 6-month followup; coverant therapy was the most successful technique (20 percent success) and breath holding the least successful-no success (40,49).…”
Section: Discussion Of the Listingmentioning
confidence: 99%
“…Keutzer and associates' careful study evaluated several techniques. They revealed a 23 percent success rate at the end of treatment and 12 percent at the 6-month followup; coverant therapy was the most successful technique (20 percent success) and breath holding the least successful-no success (40,49).…”
Section: Discussion Of the Listingmentioning
confidence: 99%
“…Similar results have been obtained by other investigators. With regard to immediate treatment results, Keutzer ( 8 ) found that none of the demographic data, Journal of Clinical Psychology, July, 1976, Vol. Sf?,No.…”
Section: Number Of Cigarettes Smoked Per Weekmentioning
confidence: 99%
“…As noted above, when reliable treatment effects do occur, they decrease rapidly during the first month, and continue to decrease sharply until the third month, where they level off, with some small additional decrease through the fi rst year (17)(18)(19)(20)(21)(22)(23)(24). With few notable exceptions (15,(57)(58)(59), most studies do not give the complete picture of relapse.…”
Section: Recidivism: the Major Problemmentioning
confidence: 99%
“…The long-term smoking cessation rates obtained in the many large-scale smoking control programs are little more encouraging than those in the general population (15,16). When reliable treatment effects do occur, they decrease rapidly during the first month, and continue to decrease sharply until the third month, where they level off, with some small additional decrease through the fi rst year (17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%